ANALISIS SOAL UJIAN BIOLOGI SEMESTER I SISWA KELAS X SMA NEGERI 9 SIJUNJUNG TAHUN PELAJARAN 2013/2014 - Sari, Novelia Handika (Pendidikan Biologi, 2014)
Analysis of items is an activity that can help improve the test quality. This research is aimed to provide information about validity, reliability, difficulty index, discrimination power and affectiveness options on items of the biological examination in first semester at X class at SMAN 1 in Sijunjung in academic year 2013/2014. This research is a descriptive research in which the researcher describes and interprets the data as it is. From the data analysis, it can be concluded that the validity problem (0,19) is in the low criteria, the reliability (0,92) is in the high criteria, the difficulty index (0.33) is in the adequate criteria, discrimination power (0, 11) is in the bad criteria. Effectiveness options with effective option key (19 items), and (21 items) ineffective option key, rapscallion effective option (3 items), and (37 items) rapscallion ineffective option. In terms of validity, reliability, difficulty index, discrimination power and effectiveness options, there are 2,5% meet with good criteria and 97,5% do not meet with good criteria.